2011
DOI: 10.1021/jp205992w
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Germanium Nanoparticle–Single-Wall Carbon Nanotube Free-Standing Anodes for Lithium Ion Batteries

Abstract: Germanium nanoparticles (Ge-NPs) were synthesized through a one-step chemical vapor deposition process and were included in a hybrid free-standing single-wall carbon nanotube (SWCNT) electrode. The Ge-NPs were characterized through scanning electron microscopy and Raman spectroscopy to confirm the presence of crystalline nanoparticles with average diameters of 60 nm. Electrochemical testing of the Ge-NPs shows high reversible lithium ion capacity up to 900 mAh g–1 and a Coulombic efficiency of 96% on the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 26 publications
1
93
0
1
Order By: Relevance
“…Due to the 3-dimensionality of the bulk CNT network within an electrode, the volume changes of bismuth associated with charge and discharge cycles may be accommodated without a net loss of Bi-CNT electrical contact, especially since this general phenomenon has been observed with other anode materials such as silicon and germanium in lithium based batteries. [17][18][19][20][21][22] In addition to current collection, the CNT substrate is lighter weight and much more corrosion resistant than metal foils and the 3-D nature of the CNT substrate allows for electrolyte and ion access. 23,24 The weight reduction by eliminating metal foils can be significant where up to 76% electrode weight savings at the cell level can be realized.…”
mentioning
confidence: 99%
“…Due to the 3-dimensionality of the bulk CNT network within an electrode, the volume changes of bismuth associated with charge and discharge cycles may be accommodated without a net loss of Bi-CNT electrical contact, especially since this general phenomenon has been observed with other anode materials such as silicon and germanium in lithium based batteries. [17][18][19][20][21][22] In addition to current collection, the CNT substrate is lighter weight and much more corrosion resistant than metal foils and the 3-D nature of the CNT substrate allows for electrolyte and ion access. 23,24 The weight reduction by eliminating metal foils can be significant where up to 76% electrode weight savings at the cell level can be realized.…”
mentioning
confidence: 99%
“…Not only does this represent many orders of magnitude improvement compared to the MEMS literature, but it approaches the speed of heavily loaded transistors with the potential for far lower power dissipation. Other major applications of freestanding CNT films include sensors [8], energy storage [9], and photovoltaic devices [10].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Demonstrating this double protection approach, Xue et al and Li et al demonstrated, separately, the much improved specific capacity, cycling performance, and rate capability of Ge@C/RGO nanocomposites, arising from the combined buffer and structural stability of the electrode [84,85]. In addition to carbon coating, combining Ge nanostructures and porous carbon had been shown to improve the cycling retention of the Ge-based anodes [87,88]. For instance, Ge NW-porous carbon composite anode displayed better stability and higher specific capacity, indicating a synergistic effect between the two components [87].…”
Section: Carbon Coatedmentioning
confidence: 99%
“…In addition to carbon coating, combining Ge nanostructures and porous carbon had been shown to improve the cycling retention of the Ge-based anodes [87,88]. For instance, Ge NW-porous carbon composite anode displayed better stability and higher specific capacity, indicating a synergistic effect between the two components [87]. A nanocomposite consisting of hierarchically porous Ge and modified carbon, synthesized via a facile hydrothermal method followed by annealing, had shown superior electrochemical performance, mainly due to the increase in electrode conductivity and buffering to accommodate the volume changes during cycling [88], as displayed in Figure 5(d).…”
Section: Carbon Coatedmentioning
confidence: 99%